Three dimensional reconstruction of therapeutic carbon ion beams in phantoms using single secondary ion tracks - Reinhart, Anna Merle; Renkamp, Claudia Katharina; Martišíková, Mária (Physics in medicine and biology, 2017)
Carbon ion beam radiotherapy enables a very localised dose deposition. However, even small changes in the patient geometry or positioning errors can significantly distort the dose distribution. A live, non-invasive monitoring system of the beam delivery within the patient is therefore highly desirable, and could improve patient treatment. We present a novel three-dimensional method for imaging the beam in the irradiated object, exploiting the measured tracks of single secondary ions emerging under irradiation. The secondary particle tracks are detected with a TimePix stack—a set of parallel pixelated semiconductor detectors. We developed a three-dimensional reconstruction algorithm based on maximum likelihood expectation maximization. We demonstrate the applicability of the new method in the irradiation of a cylindrical PMMA phantom of human head size with a carbon ion pencil beam of ##IMG## [http://ej.iop.org/images/0031-9155/62/12/4884/pmbaa6aebieqn001.gif] $226$ MeV u −1 . The beam image in the phantom is reconstructed from a set of nine discrete detector positions between ##IMG## [http://ej.iop.org/images/0031-9155/62/12/4884/pmbaa6aebieqn002.gif] $-80^°$ and ##IMG## [http://ej.iop.org/images/0031-9155/62/12/4884/pmbaa6aebieqn003.gif] $50^°$ from the beam axis. Furthermore, we demonstrate the potential to visualize inhomogeneities by irradiating a PMMA phantom with an air gap as well as bone and adipose tissue surrogate inserts. We successfully reconstructed a three-dimensional image of the treatment beam in the phantom from single secondary ion tracks. The beam image corresponds well to the beam direction and energy. In addition, cylindrical inhomogeneities with a diameter of ##IMG## [http://ej.iop.org/images/0031-9155/62/12/4884/pmbaa6aebieqn004.gif] $2.85$ cm and density differences down to ##IMG## [http://ej.iop.org/images/0031-9155/62/12/4884/pmbaa6aebieqn005.gif] $0.3$ g cm −3 to the surrounding material are clearly visualized. This novel three-dimensional method to image a therapeutic carbon ion beam in the irradiated object does not interfere with the treatment and requires knowledge only of single secondary ion tracks. Even with detectors with only a small angular coverage, the three-dimensional reconstruction of the fragmentation points presented in this work was found to be feasible.